MiRNA-loaded MSC exosomes restore autophagy flux for acute pancreatitis therapy - Zeng, Haojie; Wu, Tonghua; Luo, Si; Zeng, Anxiang (Frontiers in Immunology, 2025)
Acute pancreatitis (AP) is an unpredictable and potentially fatal disease. Currently, it is believed that the pathological mechanism of AP is closely related to autophagy imbalance, abnormal activation of inflammatory signals, and impairments in cell damage repair. Autophagy exhibits a double-edged sword effect of “activation accompanied by flux impairment” in AP. In this article, a systematic review is conducted on how mesenchymal stem cells (MSCs) and their secreted exosomes deliver functional miRNAs, targeting and regulating pathways such as PI3K/AKT/mTOR to achieve multiple effects including anti-inflammation, regeneration promotion, and restoration of autophagy homeostasis, providing new strategies for AP treatment. Current research challenges focus on the standardization of exosome preparation, optimization of miRNA delivery efficiency, and long-term safety evaluation. Further elucidation of the “cell-vesicle-miRNA-target pathway” cascade network, combined with multi-omics technology to develop precise intervention programs, is needed to advance AP treatment from mechanistic exploration to clinical translation.